The practice of sport psychology: telling tales from the field - Patrick, T. (2005)
The professional practice of sport psychology has received a tremendous amount of attention over the past two decades. Among the various studies and discussions to date, the most desirable and undesirable sport psychology consultant characteristics have been reported (Orlick & Partington, 1987); boundaries for sport science and psychology trained practitioners in applied sport psychology have been suggested (Taylor, 1994); and various models of delivery have been examined (Hardy & Parfitt, 1994). Recently, Andersen (2000) and Tenenbaum (2001) have called for a further examination of the process of sport psychology consultant-athlete interactions. For example, Petitpas, Giges and Danish (1999) identified congruence, empathy and unconditional positive regard as important facilitative conditions in optimizing client-practitioner relationships. Many others have discussed the importance of establishing trust and respect as important factors relating to effective sport psychology service delivery (e.g. Halliwell, Orlick, Ravizza & Rotella, 1999; Ravizza, 2001). In order to further our understanding regarding the process of sport psychology practitioner-athlete interactions, a phenomenological inquiry was conducted in order to examine various lived experiences and associated meanings regarding the practice of sport psychology. The focus of this study was to describe and interpret the socially generated and shared intersubjective meanings operative within the service delivery of applied sport psychology. To this end, various meanings emerged as a result of the study of the practice of sport psychology. First, multiple identities were experienced by the practitioners and these created tensions both within the practitioner and with others in their immediate environment. Second, the practitioners' various roles and related actions were the result of negotiated realities that involved all members associated with their respective communities of practice. Finally, reflexive actions associated with practice occurred as the result of a number of contextual and internal considerations that occurred before, during and after incidents of practice. It was felt that by closely examining the nature of the interactions and individual perceptions of those involved in the process of sport psychology service delivery, a positive contribution could made to the literature pertaining to the practice of sport psychology.